An evolutionary analysis of the GH57 amylopullulanases based on the DOMON_glucodextranase_like domains. (26th June 2012) - Jiao, Yu‐Liang; Wang, Shu‐Jun; Lv, Ming‐Sheng; Fang, Yao‐Wei; Liu, Shu
Abstract Thermostable amylopullulanase (TAPU) is valuable in starch saccharification industry for its capability to catalyze both α‐1, 4 and α‐1, 6 glucosidic bonds under the industrial starch liquefication condition. The majority of TAPUs belong to glycoside hydrolase family 57 (GH57). In this study, we performed a phylogenetic analysis of GH57 amylopullulanase (APU) based on the highly conserved DOMON_glucodextranase_like (DDL) domain and classified APUs according to their multidomain architectures, phylogenetic analysis and enzymatic characters. This study revealed that amylopullulanase, pullulanase, andα‐amylase had passed through a long joint evolution process, in which DDL played an important role. The phylogenetic analysis of DDL domain showed that the GH57 APU is directly sharing a common ancestor with pullulanase, and the DDL domains in some species undergo evolution scenarios such as domain duplication and recombination.